Determinants of Dementia Among the Elderly in Jakarta, Indonesia - Miciko Umeda; Aris Widiyanto; Dedy Muhdiana; Lily Herlina; Joko Tri Atmojo; Bhisma Murti (Journal of Epidemiology and Public Health, 2025)
Background: The incidence of dementia rises sharply, and it is expected to grow worldwide in the decades ahead. This study aimed to investigate the determinants of dementia among the elderly in Jakarta, Indonesia.Subjects and Method: A cross-sectional design was employed in the Aisyah organization at Jakarta City, Indonesia. A total of 65 elderly people were selected using Stratified random sampling. The dependent variable was dementia. The independent variables were education, occupation, married status, and exercise routine. The dementia was assessed using the Mini-Mental State Examination (MMSE) questionnaire, which was translated into Bahasa. Results: The participants had an education level of high school or below (52.31%), were not married (53.85%), and were not working (55.38%). The majority reported frequent exercise (92.31%), and 44.62% were identified with dementia. Bivariate analysis showed that higher education (OR = 0.92; 95% CI= 0.26 to 3.22; p= 0.002) and being married (OR= 0.94; 95% CI= 0.34 to 2.61; p= 0.020) were significantly associated with lower dementia risk. Exercise routine showed a strong protective effect (OR = 0.17; 95% CI= 0.01 to 1.79; p= 0.043), while occupational status was not significantly associated (p= 0.074). In multivariate analysis, only exercise routine remained significantly associated with dementia (OR= 0.17; 95% CI= 0.01 to 1.78; p= 0.042), suggesting it as an independent protective factor after controlling for confounders.Conclusion: Regular physical activity was identified as a significant protective factor against dementia among the elderly. Promoting exercise may be an effective strategy for dementia prevention in this population.